Editorial - Cock, Ian E. (Pharmacognosy Communications)
Dear Readers and Authors, I am pleased to bring you Volume 13, Issue 4 of Pharmacognosy Communications. In this issue, we present a review of the use of Ayuvedic plants to treat gastrointestinal; bacterial infections. This review also summarises Ayuverdic principles and thereby explains the selection of plants for this purpose. This issue also presents a comprehensive review of the use of cyanobacterial extracts and isolated compounds to treat cancer. Additionally, we present two studies evaluating the anti-bacterial activity of Rubus idaeus L. (raspberry) and Phragmites australis (Cav.) Trin. Ex Steud. leaf extracts, respectively.